2014 IEEE 14th International Conference on Advanced Learning Technologies 2014
DOI: 10.1109/icalt.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Using Stratified Attribute Tracking (SAT) Diagrams for Learning Analytics

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Then we explicated the pattern between the difficulty level and the stratified (low, medium, high) scores of the fourth week quiz using stratified attribute tracking diagrams (Majumdar and Iyer 2014). …”
Section: Problem Posing As An Assessment Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we explicated the pattern between the difficulty level and the stratified (low, medium, high) scores of the fourth week quiz using stratified attribute tracking diagrams (Majumdar and Iyer 2014). …”
Section: Problem Posing As An Assessment Toolmentioning
confidence: 99%
“…To answer RQ2, we operationalized the quality of questions using difficulty levels of the questions. Then we explicated the pattern between the difficulty level and the stratified (low, medium, high) scores of the fourth week quiz using stratified attribute tracking diagrams (Majumdar and Iyer 2014).…”
Section: Problem Posing As An Assessment Toolmentioning
confidence: 99%
“…Earlier studies on iSAT have demonstrated its development process over three research-based design iterations (Majumdar et al 2014) and its potential to be used for learning analytics (Majumdar and Iyer 2014). In this paper, we describe the utility of iSAT for instructors.…”
Section: Resultsmentioning
confidence: 99%
“…Warriem et al (2013) tracked online learners’ performance in participation for completing and submission of assessment. Majumdar and Iyer (2014) studied consistency of survey responses across different questions asked to understand student’s perception, using iSAT. Readers who are interested in details of evolution of iSAT across its design iteration can refer to Majumdar et al (2014).…”
Section: More Uses Of Isat For Instructorsmentioning
confidence: 99%